Carbothermally generated copper–molybdenum carbide supported on graphite for the CO2 hydrogenation to methanol. Issue 12 (4th May 2021) - Dongil, A. B.; Conesa, J. M.; Pastor-Pérez, L.; Sepúlveda-Escribano, A.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract : The carbothermal synthesis of monometallic and bimetallic molybdenum carbide and copper supported on high surface area graphite, has been studied at 600 and 700 °C and characterised. The catalysts were tested for CO2 hydrogenation to CH3 OH. Abstract : The carbothermal synthesis of monometallic and bimetallic molybdenum carbide and copper, supported on high surface area graphite (H), has been studied by in situ XRD, XPS, D2 -TPD, TEM/STEM, TG-mass spectrometry, and N2 adsorption. The catalysts were prepared using H2 at 600 °C or 700 °C and tested in the hydrogenation of CO2 to methanol. Molybdenum carbide and oxycarbide phases were obtained, as well as hydride species, at 600 °C on both monometallic Mo x C/H and bimetallic CuMo x C/H in a similar proportion. Upon increasing the temperature up to 700 °C, the formation of metallic Mo is favourable. Although this is observed on supported Mo x C and CuMo x C, the bimetallic sample is less affected by the formation of the hydride, and molybdenum carbide is also observed upon treatment at 700 °C. With regards to the catalytic performance, supported monometallic copper was not active, but copper increased the activity and selectivity of the molybdenum carbide. The yield of methanol per catalyst's weight increases upon increasing the copper loading, indicating that a cooperation reaction takes place between the smallest Cu particles in contact with the molybdenum phase. The catalysts synthesized at 700 °C are less active and less selective to methanol favouring the reverse water gas shift under the studied conditions. Interestingly, the catalysts are stable under the reaction conditions, and the detected phases by XRD of the spent catalysts suggest that the hydride species favoured transformations involving MoO x C y H z ↔ β-Mo2 C.